Droplets and Aerosols Generated by Singing and the Risk of Coronavirus Disease 2019 for Choirs. (27th August 2020) - Bahl, Prateek; de Silva, Charitha; Bhattacharjee, Shovon; Stone, Haley; Doolan, Con; Chughtai, Abrar Ahmad; MacIntyre, C Raina
Abstract: Choral singing has become a major risk during the coronavirus disease 2019 (COVID-19) pandemic due to high infection rates. Our visualization and velocimetry results reveal that the majority of droplets expelled during singing follow the ambient airflow pattern. These results point toward the possibility of COVID-19 spread by small airborne droplets during singing.